Use of 17β-estradiol for leporinus macrocephalus feminization - Pereira, Thiago Scremin Boscolo; Boscolo, Camila Nomura Pereira; Batlouni, Sergio Ricardo [UNESP] (Boletim do Instituto de Pesca, 2020)
The aim of this study was to evaluate the effects of the use of a diet supplemented with 50 or 100 mg kg-1 17β-estradiol (E2 ) for Leporinus macrocephalus feminization. Thus, one hundred and fifty fingerlings with 50 days old post-hatch were randomly distributed in fifteen experimental tanks of 90 L and fed for 60 days on a diet supplemented with 50 or 100 mg kg-1 of E2 . At the end of the experiment, sex ratios were determined through histological and macroscopic observations. Histologically, the differentiated ovaries were evidenced by the presence of numerous nests of oogonia and oocytes in primary growth stage. The female ratio (77%) for the group treated with 100 mg kg-1 E2 was significantly higher than those of control (52%) and 50 mg kg-1 treatment (48%) groups. These results obtained in this initial study indicated that 100 mg kg-1 of E2, administered over 60 days, was the most effective treatment for 50 days old L. macrocephalus post larval feminization. However, future studies with variations in the application range can bring even better results.
Utilização de 17β-estradiol para feminização de leporinus macrocephalus
Keywords: Aquaculture-species; Monosex fish populations; Native fish; Sex inversion